Football in the land of the Soviets - Viñas, Carles, 1972- (Pluto Press, 2022)
"Mistrusted and derided, instrumentalised and adored - the story of football in Tsarist and early Soviet Russia is as wild and intriguing as that of the country itself. In many ways it is the same story… Football in the Land of the Soviets offers a fresh perspective on a momentous chapter in modern political history. Carles Viñas shows how the Russian game was transformed in just a few decades: from a minor émigré pastime, to a modernising driver of society, to a vanguard for Soviet diplomacy and internationalism, and finally, with the first championship of the Soviet League in 1936, into a truly mass phenomenon. So exactly how did a bourgeois game end up as the collective passion of the Soviet working class? And why does it matter? Football in the Land of the Soviets brings these questions to the fore in this thrilling, unorthodox account of the fall of an imperial dynasty and the rise of the world's first socialist state."--publisher.